Speech at Event on Delivering for Every Woman and Every Child within a Generation, United Nations, New York, September 25, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses maternal and child deaths; developing finance; and transforming business in global health and development. He announced that the creation of the Global Financing Facility in support of Every Woman Every Child will enable countries to close the gaps in achieving the health millennium development goals, building on proven experience with results-based financing for health. The Facility will help countries mobilize additional domestic and international resources, including from domestic budgets, other bilateral and multilateral donors, the private sector, and innovative financing mechanisms.